2012
DOI: 10.1111/j.1365-2206.2012.00840.x
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of accessible service delivery on front‐line helping relationships in child welfare

Abstract: A B S T R AC TThis paper presents the results of a study comparing the impacts on helping relationships of locating front-line child protection service providers in central locations or in accessible school and neighbourhood service delivery sites. Creating easier access to front-line child protection service providers, fostering more positive community perceptions of child welfare services, improving client and service provider satisfaction with helping relationships and services, and increasing families' wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…On the one hand, scientific evidence has shown that the use of skills by professionals within intervention contexts positively influences clients' and families' engagement, client satisfaction with the services, and the effectiveness of the intervention in regard to empowering and improving parental skills, and the positive development of minors (Cameron et al 2013;Connolly and Devaney 2016;Damiani-Taraba et al 2017;Gallagher et al 2012;Gladstone et al 2014;Hedberg et al 2018;Muurinen 2019;Slettebø 2013;. Conversely, the use of these skills is influenced by the professionals' engagement and perception of themselves as caring and helping people, the professionals' experience, and the significant challenges they face at work (Damiani-Taraba et al 2017;Kemp et al 2014).…”
Section: The Theoretical Foundation Concerning Family Support Skillsmentioning
confidence: 99%
“…On the one hand, scientific evidence has shown that the use of skills by professionals within intervention contexts positively influences clients' and families' engagement, client satisfaction with the services, and the effectiveness of the intervention in regard to empowering and improving parental skills, and the positive development of minors (Cameron et al 2013;Connolly and Devaney 2016;Damiani-Taraba et al 2017;Gallagher et al 2012;Gladstone et al 2014;Hedberg et al 2018;Muurinen 2019;Slettebø 2013;. Conversely, the use of these skills is influenced by the professionals' engagement and perception of themselves as caring and helping people, the professionals' experience, and the significant challenges they face at work (Damiani-Taraba et al 2017;Kemp et al 2014).…”
Section: The Theoretical Foundation Concerning Family Support Skillsmentioning
confidence: 99%
“…This response in Canada reflected a paradigm shift in the secondary intervention sector whereby the nature of intervention changed from protection and treatment, hallmarks of statutory intervention, to prevention and promotion of family needs (Trocme and Chamberland, 2003). Cameron et al (2013) argued that the Canadian Government’s differential response involved secondary intervention and tertiary child protection authorities working collaboratively. This collaboration was focused on developing trusting relationships with families, changing service philosophy or intentions and establishing physical settings for the delivery of services within the communities.…”
Section: Secondary Intervention Models Of Supportmentioning
confidence: 99%
“…This collaboration was focused on developing trusting relationships with families, changing service philosophy or intentions and establishing physical settings for the delivery of services within the communities. The secondary intervention sector in Canada has a strong mandate to support families to reduce the fear and stigma associated with the need for support, access to support services being made more available and encouragement of families to request support (Cameron et al , 2013). This approach is also evident within Australia, and similarly to Canada, this secondary tier of support receives children who have significant cumulative harm exposure.…”
Section: Secondary Intervention Models Of Supportmentioning
confidence: 99%
“…A persistent challenge for child welfare practitioners internationally has been developing meaningful relationships with family members (Cameron et al, 2013). The importance of valuing human relationships is a very basic belief and underpinning premise in Family Support.…”
Section: Relationship Based Practicementioning
confidence: 99%
“…While it is argued that practitioners are heavily constrained by competing demands on their time it is also argued that creating positive helping relationships is central to improving outcomes in child welfare (Cameron et al, 2013). It is also noted that addressing a negative behaviour is more effective if there is an existing relationship between the practitioner and the family members.…”
Section: Relationship Based Practicementioning
confidence: 99%